Psychological and nutritional factors as correlates of wellbeing of female athletes in Oyo State (2018)
This study was carried out in order to find out the psychological and nutritional factors as correlate of wellbeing among female athletes in Oyo State. The descriptive survey research design was employed due to its suitability to the study objective. The population for the study was female athletes in Oyo State while a sample of 100 respondents was purposively drawn across twelve (12) major sports represented by the athletes. A self- structured validated dose ended 4-point Likert scale instrument was used for data collection. Four hypotheses were tested. The collected questionnaire were coded and analysed using inferential statistics of multiple regression to test the hypotheses at 0.05 alpha level. In conclusion, the researchers found that psychological and nutritional variables such as self-efficacy, self-esteem, late eating, snacking and skipping meal significantly correlate with wellbeing of female athletes in Oyo State Sports Council. It therefore recommended that coaches and athletes should endeavor to watch out for those psychological factors and strengthen the psychological state needed for wellbeing, nutritional needs of the athletes should be taken care of